Evaluating Design Thinking in Mathematics Students: The Impact of AI Utilization and Digital Literacy - Tommy Wijaya; Xiaoli Chen; Sidik Purnama (JINEA: Journal of Innovation in Education and Learning, 2026)
The accelerated expansion of artificial intelligence (AI) in mathematics education has transformed instructional practices; however, its effectiveness in fostering higher-order cognitive skills remains inconclusive. Although AI-enabled learning environments provide adaptive feedback and personalized support, limited student digital literacy often restricts meaningful and critical engagement with these technologies. This suggests that AI integration alone is insufficient to develop design thinking skills without adequate learner readiness. Accordingly, this study investigates the structural relationships among AI utilization, digital literacy, and design thinking in mathematics education, with particular emphasis on the mediating role of digital literacy. A quantitative research design was adopted, drawing on survey data collected from undergraduate students and analyzed using structural equation modeling. The results indicate that AI utilization explains 35% of the variance in digital literacy, while the combined effects of AI utilization and digital literacy account for 48% of the variance in students’ design thinking skills. Furthermore, digital literacy exhibits a statistically significant mediating effect, strengthening the influence of AI utilization on design thinking outcomes. These findings demonstrate that the pedagogical effectiveness of AI in mathematics education depends on the development of students’ digital competencies and provides a conceptual framework to guide future instructional design and research.